Pendugaan Umur Simpan Saus Tomat Homemade Menggunakan Model Arrhenius pada Suhu Penyimpanan Berbeda - Meikapasa, Ni Wayan Putu; Pravitri, Kartika Gemma; Arzani, Lalu Danu Prima (Jurnal Teknologi dan Mutu Pangan, 2024)
Homemade tomato sauce products have the advantage of having a composition that can be ensured to contain minimal harmful chemicals. However, like other processed products, of course, the product will experience a decrease in quality along with the length of storage time. This study aims to determine changes in the quality of tomato sauce produced on a home scale (homemade ketchup) during one month of storage at storage temperatures of 10oC, 250oC, and 350oC. The method used to predict shelf life is the Arrhenius calculation model, which observes changes in pH, aw, and Total Microbes. The findings showed that the pH of tomato sauce tended to decrease with the length of storage time. The number of microbes increased with the increasing temperature and length of storage. Meanwhile, temperature and length of storage did not affect water activity. However, aw tends to increase with the temperature and length of storage. The results of estimating the shelf life with the Arrhenius model based on the water activity (aw) parameter showed that the shelf life of the sauce was 151.75 days with a quality decline rate of 0.001068/day at a storage temperature of 10oC; 96.07 days with a quality decline rate of 0.001685/day at a storage temperature of 25oC and 72.6 days with a quality decline rate of 0.002227/day at a storage temperature of 35oC. The implications of this study indicate that storage at 10oC can extend the shelf life of both tomato sauce products, so producers and consumers need to consider the optimal storage temperature based on the results of this study.